Impact of taxation policy changes on benefits in kind under the harmonization of tax regulations law: Implications for compliance and economic sustainability - Shiga, Briliana Aiko; Rosdiana, Haula (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: In 2021, the Indonesian government enacted the Harmonization of Tax Regulations Law/Harmonisasi Peraturan Perpajakan (HPP Law), which introduced several policy changes in taxation, including the taxation of benefits in kind. Benefits in kind, now subject to Income Tax, may lead to complexity regarding the application of value added tax (VAT) on benefits in kind used for personal consumption and gratuitous gifts. This study aims to analyze the changes in taxation policy on benefits in kind following the implementation of the HPP Law, particularly its impact on personal use and gratuitous gifts of benefits in kind already subject to VAT. Methods: This research employs a qualitative approach, collecting data through field studies involving in-depth interviews and literature reviews. The findings indicate that the policy change increases administrative burdens for companies, risks of tax bracket shifts for employees, and complexities in determining the correct tax objects among benefits in kind, personal use, and gratuitous gifts. Findings: Companies face increased complexity in valuing, reporting, and adjusting payroll systems to include in-kind benefits as taxable income, leading to higher administrative costs and risks of reporting errors. Employees, particularly those in middle to upper-income brackets, may experience higher tax liabilities as in-kind benefits push their taxable income into higher tax brackets, increasing personal tax burdens and affecting Article 21 Income Tax obligations borne by employer. Conclusions: The taxation of benefits in kind under the HPP Law introduces complex regulatory challenges for businesses and employees. Increased compliance costs, administrative burdens, and potential tax rate shifts highlight the need for effective policy implementation strategies. Novelty/Originality of this Article: This study provides a comprehensive analysis of the intersection between Income Tax and VAT under the new taxation of in-kind benefits—an area that remains underexplored in Indonesian tax policy research.